81 Assessment of a novel, web-based, open-access training resource for junior trainees in echocardiography. (4th June 2021) - Chapman, Sally; O'Toole, Laurence; Fent, Graham; Mackay, Jane
Abstract : Introduction: Transthoracic Echocardiography (TTE) is a vital diagnostic tool in modern medicine. Training in TTE to the level of the national standard of accreditation required by the British Society of Echocardiography (BSE), which is necessary for independent practice, is arduous and teaching needs are often sacrificed to service demands. TTE training involves the acquisition of detailed anatomical, physiological and pathological knowledge of cardiac function in both health and disease as well as 2 to 3 years of hands-on experiential training. These demands have led to a severe shortfall of trained sonographers in the UK resulting in recurrent waiting list crises, which have an adverse impact on patient care. Web-based teaching is accessible, time efficient and economical and could be an effective adjunct to practical teaching in echocardiography. Currently, there is no free, open-access and comprehensive resource for trainee sonographers working to the British Society of Echocardiography curriculum. Methods: Funded by a grant from Health Education England, we have created a website to host the lectures, illustrative cases and demonstration videos used in the standardised training programme for TTE for junior sonographers in Sheffield Teaching Hospitals NHS Trust. The website [ figure 1 ] is accessible on smartphones, tablets and PCs, and can be accessed at home and work. The content begins with basic concepts, moves to demonstrate aspects of image acquisition and optimisation, discusses the major cardiac pathologies and advises on image interpretation and reporting. Cardiac physiologists and cardiology registrars in our region were surveyed regarding their attitude to web-based echo learning and their impressions of the initial development of the website after development of 3 of the training modules. Results: Twenty-nine trainees responded to the initial survey with 18 (62%) being cardiac physiologists. 90% accessed online learning at least occasionally, most commonly on a weekly basis. The BSE website was their most frequently accessed website as an echo training resource. Of the respondents, 93% reported that they would use an online echo training resource with 83% stating that using an online training resource would improve confidence in echo reporting. Over 90% felt that an online resource would improve their understanding of TTE. All of those who completed the follow up survey (n=10) found the website helpful, said that they would continue use the site and would recommend the site to other trainees. Conclusion: This training website seeks to provide a single source of access to the key knowledge needed for cardiac physiologists and registrars training in TTE. Our survey suggests that junior trainees will find it to be a useful adjunct to their experiential learning. The project is to continue to create content and we hope to open the website as a free, national open-access learning resource. Conflict of Interest: None